Kenya : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix provides an assessment of the financial regulations as a basic framework for public expenditure management and control in Kenya. The paper discusses a number of 'external' factors that have led to a deterioration of formal implementation and control mechanisms, as well as recent efforts that have been undertaken to improve them. The paper also discusses various aspects of monetary policy in Kenya, including the instruments available to the monetary authorities, current challenges in the area of monetary control, and the state of financial markets in Kenya.